High efficiency T-type converter - Saxena, Aryaman Rawar (Nanyang Technological University, 2022)
Multilevel Converters (MLC) are preferred compared to two-level converters thanks to their low harmonic injection, even at low switching frequency values, accepting high power as well as high voltage levels at small size. Among reduced switching devices count MLCs is the T-type topology. The aim of this project is to understand a T-Type Multilevel Converter as well as to make a program for DC side closed loop control and run the inverter with an RL Load and an induction motor.